A Global Perspectiveon External Positions - Milesi-Ferretti, Gian (IMF Working Papers; Working Paper ;, 2005)
This paper highlights the increased dispersion in net external positions in recent years, particularly among industrial countries. It provides a simple accounting framework that disentangles the factors driving the accumulation of external assets and liabilities (such as trade imbalances, investment income flows, and capital gains) for major external creditors and debtors. It also examines the factors driving the foreign asset portfolio of international investors, with a special focus on the weight of U.S. liabilities in the rest of the world's stock of external assets. Finally, it relates the empirical evidence to the current debate about the roles of portfolio balance effects and exchange rate adjustment in shaping the external adjustment process.